(3GdehTM Ydi cGajI GHf GdMGLHs - (3TeS GdOjf GdNHjUis; (3GdNHjUj , eMeO Hf CHj HcQ Hf eMQR, TeS GdOjf GdNHjUj,J (B731 (3g` s
(3ChdgG (B:s
(3G GdcdeI Cj GdJj hVYJ aj GUWdGM GdfMGI s
(3BNQgG (B:s
(3Je GdcJGH HYhf ef Edjg GdeQLY hGdeBH s
(3Vef eLehY , JQJjHgG (B: 2s
(3GdfSNI HgG MhGTs
(3HBNQgG fbhd eNJdaI HebOGQ CQHY hQbGJs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdfMhs